Antioxidant Property of Centaurea solstitialis L. from Konya, Turkey - Tekeli, Yener; Sezgin, Mehmet; Aktumsek, Abdurrahman (Asian Journal of Chemistry, 2010)
In this study, Centaurea solstitialis L. was extracted with petroleum ether using a Soxhlet apparatus. The antioxidant properties of plant extract and synthetic antioxidant compounds were evaluated using different antioxidant tests, including reducing power, DPPH free radical scavenging activity and total phenolic compound. Results were compared with standard butylated hydroxytoluene and butylated hydroxyanisole.